2018
DOI: 10.1111/jvim.15118
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and associated factors for bacterial colonization of intravenous catheters removed from dogs in response to clinical complications

Abstract: BackgroundInfection rate associated with intravenous (IV) catheter placement is emerging as an important issue in small animal veterinary medicine, mostly because of the economic costs associated with these infections. Identification of possible associated factors may provide useful information for the surveillance and prevention of such infections.ObjectivesTo determine the incidence of positive bacterial cultures obtained from IV catheters used in dogs hospitalized for at least 48 hours and removed because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…Reported incidence of IVC infection in dogs and cats range from 15.4 to 22% . In dogs, bacteria isolated from IVCs are of gastrointestinal or environmental origin with Staphylococcus spp and Acinetobacter spp being the most frequently isolated bacteria. Furthermore, the bacteria isolated from IVCs in dogs are multidrug resistant, suggesting a negative impact on antibiotic treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Reported incidence of IVC infection in dogs and cats range from 15.4 to 22% . In dogs, bacteria isolated from IVCs are of gastrointestinal or environmental origin with Staphylococcus spp and Acinetobacter spp being the most frequently isolated bacteria. Furthermore, the bacteria isolated from IVCs in dogs are multidrug resistant, suggesting a negative impact on antibiotic treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, PIVC use is generally associated with mechanical, inflammatory, and infectious complications [ 3 , 4 ]. Specifically, the rate of catheter-related infections is an important emerging issue in small animal veterinary medicine, mostly due to high morbidity, increased costs, and duration of treatment [ 14 , 24 ]. Furthermore, zoonotic risk arising from multi-drug resistant bacterial infections should be considered [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In studies conducted in dogs, a median indwell time of PIVCs ranging from 48 to 72 h was recorded [ 11 , 14 , 29 ], whereas the time of permanence in situ of PIVCs recorded in cats by Bush et al was 28.8 h when devices were removed due to discharge, and 16.6 h when the withdrawal was consequent to other reasons; a further study found that PIVCs remained in place for a time >72 h in more than 80% of the included cats [ 12 ]. The permanence time of PIVCs recorded in dogs in our study was shorter than that reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this was not directly assessed in the present study, 10 animals did experience insertion site reactions such as erythema and edema, which may have been indicative of incipient local infection. In studies of dogs and cats with peripheral IV catheters, the catheters of patients exhibiting clinical signs of infection were found to be colonized with bacteria between 39.6% and 42.9% of the time in dogs and cats, respectively 13,14 …”
Section: Discussionmentioning
confidence: 99%